ANALISIS DAMPAK COVID 19 PADA PENERAPAN PEMBELAJARAN DARING DAN KETERAMPILAN SISWA PADA UPT SDI BENTENG N0. 62 KEPULAUAN SELAYAR - Akbar .; Muhammad Fahreza W (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2022)
This study aims to describe the impact of Covid 19 on the application of online learning and student skills at Upt Sdi Benteng No.62 Kepulauan Selayar. The researcher uses a qualitative approach, with the type of phenomenological research, which is based on a phenomenon that occurs around the city that obtains the required information. The purpose of this study is to present the results of research regarding the implementation of online learning for grade VI A Elementary School students during the Covid-19 pandemic. This research was conducted on class VI students of UPT SDI BENTENG NO. 62 KEPULAUAN SELAYAR, South Sulawesi Province with a total of 23 students in class VI A. The research data is about the implementation of online learning for class VI A students during the Covid-19 pandemic at UPT SDI BENTENG NO. .62 SELAYAR ISLANDS, South Sulawesi Province from the results of observations, interviews and documentation. The data in the study consisted of primary data and secondary data. Primary data is data from resource persons (teachers) class VI A UPT SDI BENTENG NO. 62 KEPULAUAN SELAYAR, and class VI A students. Secondary data in the archives, written data and documents used to support the data that has been obtained. Keywords: Application of Online Learning, Student Skills